Evaluation de quelques paramètres biochimiques chez des femmes enceintes hypertendues de la région de Mostaganem. - Benani, latifa; Berrahil, nor el islam (My University, 2022)
High blood pressure (hypertension) is the most common medical complication during pregnancy. It is potentially dangerous. It is one of the leading causes of maternal, fetal and neonatal morbidity and mortality. The objective of our study is to determine the biochemical profile, risk factors as well as complications related to the development of high blood pressure in pregnant women in the Mostaganem region. We conducted a 1-month study including 30 women aged from 20 to 42 years old followed at the maternity ward of Lala Khiera, Mostaganem. Our population includes 15 hypertensive women and 15 healthy women. An adapted questionnaire containing 23 hypertension-related items was distributed to all women to determine the main characteristics of the study population. The biochemical profile of all women was determined by determination of blood glucose, urea, creatinine, transaminases (TGO and TGP), prothrombin, quick time, TCK and proteinuria assay. This study shows that:  The age group most affected by high blood pressure during pregnancy is between 30 and 40 years of age, estimated at 60%.  More than 50% of hypertensive pregnant women are obese.  Chronic hypertension is the majority with a percentage of 33.33% followed by gestational hypertension (26.66%), over-added pre-eclampsia (26.66%) and finally pre-eclampsia with a percentage of 13.33%.  Chronic and gestational hypertension affects pregnant women between the ages of 30-40 much more, while pre-eclampsia and added pre-eclampsia affect women much more, where the age varies between 20-30 years.  Blood type A is the most represented in our population of hypertensive pregnant women (60%).  73.33% of hypertensive pregnant women are multiparous.  Diabetes is the main comorbidity of hypertension during pregnancy (33.33%).  In pregnant women with hypertension, the percentage of stillbirths is high compared to that observed in healthy women (40% vs. 13.33%).  40% of our hypertensive population are pre-eclampse women (proteinuria > 0.3 g/24h).  Abnormalities in the biochemical profile of hypertensive pregnant women are mainly presented by hyperglycemia, an increase in the level of TGO and TCK (p˂0.001). All of our results show that during pregnancy, high blood pressure has deleterious effects on the course of pregnancy both maternal and fetal.
Keywords: Pregnancy; High blood pressure; Biochemical profile; Risk factors; Complications